Flourishing Young Adults: Lived Lifelong Learning Experiences through Civic Participation - Junghwan Kim; Christiana G. Horn; Kasie T. Crall; Lisa B. Friesen (Adult Education Research Conference, 2019)
This phenomenological study aims to examine the lived learning experiences of eight young adults who participated in two AmeriCorps organizations and how those experiences impacted their civic engagement.
Keywords: lifelong learning; civic engagement; young adults; AmeriCorps